Channel modeling and bit error rate performance simulation for fixed broadband wireless access system - Tang, Min Keen (2005)
Wireless Local Area Networks (WLANs) have emerged as a powerful architecture capable of supporting the requirements of broadband wireless communications. This research deals with bit error rate (BER) performance simulation of a fixed broadband wireless access (FBWA) system that employs the Institute of Electrical and Electronics Engineers 802.11a WLAN standard at 5.8 GHz band. The specific research site takes place in newly constructed hostels with the transmitting base station at Wireless Communication Center in Universiti Teknologi Malaysia. In order to represent the real working environment when the telecommunication system is analyzed, radio channel characteristic must be modeled. In particular, the BER performance is a basic criterion for evaluating the quality of a digital signal transmission system. Hence, an effective channel model that yields both the predicted delay profile and received signal level at any possible receiver location is developed. Ray tracing propagation prediction that is a promising technique on which location specific models can be based is applied in this research. The prediction results are then enhanced with field measurement at the real environment. A powerful electronic design automation software simulator named Advanced Design System is brought forward for system modeling and performance simulation template development. The modeled transmitter and receiver are tested conforming to the related standards before the system performance is theoretically validated. Simulated BER performances under the modeled channels are found varying from 1.0399X10-2 until 1.6250X10-8 at 20dB of energy per bit to noise density (Eb/N0). The results are unpredictable without the simulations. This signifies the importance of site-specific BER performance simulation for a FBWA system. With the highlighted methodology in this research, it can drastically increase the productivity and effectiveness of the FBWA system planning at any locations.